Intraoperative management for ex-utero intrapartum treatment: focusing on the fetus - Woosuk Chung; Chaeseong Lim (Anesthesia and Pain Medicine, 2021)
Ex-utero intrapartum treatment (EXIT) is a method of securing the airway of a fetus while maintaining umbilical circulation for newborns who are experiencing life-threatening airway obstruction. Cesarean section is completed only after ensuring the neonate’s safety. However, managing the airway of a neonate while maintaining umbilical circulation is a major challenge for anesthesiologists. Anesthesiologists must understand the physiology of both the mother and fetus, and extensive discussions with obstetricians, pediatricians, otolaryngologists, and nursing staff prior to the procedure are essential. This review provides an overview of the EXIT and details of airway management for neonates.